Rapid identification of PAX2/5/8 direct downstream targets in the otic vesicle by combinatorial use of bioinformatics tools - Ramialison, Mirana; Aghaallaei, Nargessadat; Ettwiller, Laurence; Wittbrodt, Beate; Wittbrodt, Joachim (Genome biology, 2008)
The pax2/5/8 genes belonging to the PAX family of transcription factors are key developmental regulators that are involved in the patterning of various embryonic tissues. More particularly, their function in inner ear specification has been widely described. However, little is known about the direct downstream targets and, so far, no global approaches have been performed to identify these target genes in this particular tissue.
Gesehen am 16.05.2017